Evaluation of In Vivo Antidiarrheal Activity of 80% Methanolic Leaf Extract of Decne (Santalaceae) in Swiss Albino Mice - Meseret Yigzaw Teferi MSc; Mohammedbirhan Abdulwuhab MSc; Jibril Seid Yesuf MSc (SAGE Publishing, 2019)
The leaf of Osyris quadripartita is traditionally used for the management of diarrhea in different parts of Ethiopia. However, its use has not been scientifically validated for its efficacy. The aim of this study was to investigate antidiarrheal activity of hydroalcoholic leaf extract of O. quadripartita in mice models. Different doses of the methanolic leaf extract of O. quadripartita (100, 200, and 400 mg/kg) were tested for antidiarrheal activity using castor oil-induced diarrhea, enteropooling, and gastrointestinal motility models in Swiss Albino mice. The activities of the extract at different doses were compared with standard drugs and negative control groups of mice. The extract at all tested doses resulted in significant reduction ( P < .01) in number of wet feces, whereas significant reduction ( P < .01) in frequency of defecation in castor oil-induced diarrhea was seen at a dose of 400 mg/kg. It also showed a dose-dependent and significant reduction of volume of intestinal content in the enteropooling model at all tested doses and the observed results in 200 and 400 mg/kg were better than the standard drug, loperamide. However, significant antimotility effect was not observed at any of the tested doses. From these results we can conclude that methanolic leaf extract of O. quadripartita showed antidiarrheal activity.